150k views
2 votes
Which expression is equivalent to? Please help! Screenshots attached.

Which expression is equivalent to? Please help! Screenshots attached.-example-1
User Lrsppp
by
5.8k points

2 Answers

3 votes

Answer:

The expression which is equivalent to the given expression is:


(√(5))/(x^2y)

Explanation:

We are given a expression as:


\sqrt{(55x^7y^6)/(11x^(11)y^8)}

Now we know that:


55=11* 5

Hence, we get:


\sqrt{(55x^7y^6)/(11x^(11)y^8)}=\sqrt{(11* 5x^7y^6)/(11x^(11)y^8)

which is written as:


\sqrt{(5x^7y^6)/(x^(11)y^8)}

Also, we know that if n>m

Then


(a^m)/(a^n)=(1)/(a^(n-m))

Hence, we have the expression as:


=\sqrt{(5)/(x^(11-7)y^(8-6))}\\\\\\=\sqrt{(5)/(x^4y^2)

This could be given as:


=(√(5))/(√(x^4)√(y^2))

Now, we know that:


√(x^4)=√((x^2)^2)=x^2\\\\and\\\\√(y^2)=y

Hence, we get that:


\sqrt{(55x^7y^6)/(11x^(11)y^8)}=(√(5))/(x^2y)

User Whozumommy
by
5.6k points
0 votes

Answer:


(√(5) )/(x^(2) y)

Explanation:

That's a complex expression, let's simplify it, step by step, off the start, we'll simplify the 55/11:


\sqrt{ (55 x^(7) y^(6) )/(11 x^(11) y^(8) ) } = \sqrt{ (5 x^(7) y^(6) )/(x^(11) y^(8) ) }

Then we'll simplify the x's and y's:


\sqrt{ (5 x^(7) y^(6) )/(x^(11) y^(8) ) } = \sqrt{ (5)/(x^(4) y^(2) ) }

Let's split the square root in two and solve the bottom part:


\sqrt{ (5)/(x^(4) y^(2) ) } = \frac{√(5) }{\sqrt{x^(4) y^(2)} } = (√(5) )/(x^(2) y)

The solution is then:


(√(5) )/(x^(2) y)

User Max Wen
by
5.1k points